Transmission and amplification of information and properties in nanostructured liquid crystals. - Goodby, J; Saez, I; Cowling, S; Görtz, V; Draper, M; Hall, A; Sia, S; Cosquer, G; Lee, SE; Raynes, E (2008)
In recent years the design of chemical structures of liquid-crystalline materials has developed rapidly, and in many cases changed radically. Since Reinitzer's days, liquid crystals have either been classed as rodlike or disclike, with combinations of the two leading to phasmidic liquid crystals. The discovery that materials with bent molecular structures exhibited whole new families of mesophases inspired investigations into the liquid-crystal properties of materials with widely varying molecular topologies-from pyramids to crosses to dendritic molecules. As a result of conformational change, supermolecular materials can have deformable molecular structures, which can stabilize mesophase formation, and some materials that are non-mesogenic, on complexation form supramolecular liquid crystals. The formation of mesophases by individual molecular systems is a process of self-organization, whereas the mesophases of supramolecular systems are formed by self-assembly and self-organization. Herein we show 1) deformable molecular shapes and topologies of supermolecular and self-assembled supramolecular systems; 2) surface recognition processes of superstructures; and 3) that the transmission of those structures and their amplification can lead to unusual mesomorphic behavior where conventional continuum theory is not suitable for their description.